Mapping Kolb Learning Styles to Adaptive Curriculum Strategies in Geography Teacher Education: Evidence from Indonesia - Faisal Arif Setiawan; Akhmad Munaya Rahman; Sri Agustina; Noor Liana Waty (AL-ISHLAH: Jurnal Pendidikan, 2026)
Understanding students’ learning styles is essential for designing responsive higher education curricula. This study aims to map university students’ learning styles and propose an adaptive curriculum framework for geography education in Indonesia.A descriptive quantitative design was employed. Data were collected from a stratified sample of 100 undergraduate students (cohorts 2019–2022; 45% male, 55% female) at Universitas Lambung Mangkurat using Kolb’s Learning Style Inventory (LSI). Outliers (Z |3|) were removed prior to analysis. Descriptive statistics were used to identify the distribution of learning styles and mean scores across learning dimensions.The distribution of learning styles was dominated by Converging (52%), followed by Accommodating (24%), Assimilating (17%), and Diverging (7%). Mean dimension scores were AE = 23.09, AC = 21.81, CE = 19.15, and RO = 18.81, indicating a preference for active experimentation and abstract conceptualization. These findings suggest a tendency toward problem-solving and practical application among students.Based on the identified profiles and relevant literature, a conceptual adaptive curriculum model is proposed, integrating experiential learning, technology-enhanced instruction, and local geographical contexts. Such alignment may improve engagement and learning outcomes by accommodating diverse preferences.Mapping learning styles provides a basis for curriculum adaptation in geography education. However, the findings are limited by the single-institution sample, reliance on self-reported data, and ongoing theoretical debates surrounding learning-style models. Further experimental research is needed to validate the proposed framework.